Survei Sarana Dan Prasarana Pendidikan Jasmani Pada Sekolah Menengah Atas Se-Kecamatan Ngawi - Wisnugroho, Wildan Aji; Sistiasih, Vera Septi; Nurhidayat, Nurhidayat; Fatoni , Muhad (Jurnal Porkes, 2025)
The purpose of this study was to determine the state of physical education facilities and infrastructure at Senior High Schools in Ngawi District both in quantity and quality. This research uses quantitative descriptive research with a survey approach. The population of this study was high school in Ngawi sub-district and the sample was 4 schools, namely in SMA Negeri 1 Ngawi, SMA Negeri 2 Ngawi, MAN 1 Ngawi and SMAS Muhammadiyah 1 Ngawi. The data collection technique is by using observation and documentation. The data analysis used is descriptive quantitative by classifying the type of data obtained from the observation sheet. With the results of the data description obtained a mean of 12.35 and a standard deviation of 10.74, it can be categorized in the good category with a value equal to 28.50. There are some facilities and infrastructure that are in damaged condition in one of the schools, besides that there are some infrastructure facilities that are not owned by the four schools. It can be concluded that physical education facilities and infrastructure in high schools in Ngawi sub-district have a good category, it's just that there are still some equipment not owned, such as hoops and bracelets on gymnastics equipment, jumping crates on gymnastics equipment.